(untitled) (Research, Society and Development, 2021)
Gestational syphilis is a Sexually Transmitted Infection (STI) with a high prevalence and rate of vertical transmission. This is an ecological, retrospective, descriptive and analytical study that aimed to analyze the epidemiological profile of 4,073 notified cases of gestational syphilis in Paraíba between 2008 and 2018. Data were extracted from the SUS Department of Informatics - DATASUS and tabulated by TABNET using “Epidemiological and Morbidity” data from the National System of Notifiable Diseases (SINAN NET). The following variables were used: age group, education, race, area of ​​residence, mesoregion and microregion, for chi-square tests of adherence and independence, and a simple linear regression to verify the growth trend of gestational syphilis in the state. Regression and residual normality tests (Kolmogorov-Smirnov test) were performed using Excel software. The following risk groups for gestational syphilis were identified: women aged 20-39 years; with low education, brown; the urban area; the mesoregion of Mata Paraibana and the microregion of João Pessoa. The groups that received less prenatal care were: women of the yellow race, from the mesoregion of Mata Paraibana and from the microregion of Patos. Simple linear regression was statistically significant (positive beta of 0.48), indicating an upward trend in IST in the state. An aggravating factor is that a woman can be included in several risk groups at the same time. Such risk groups deserve attention from the government, in order to reduce the incidence of this STI and contribute to public policies with greater effects on disease prevention.